Clinical and Socio-demographic Determinants of Self-care Maintenance, Monitoring and Management in US Adults with Type 2 Diabetes Mellitus. (March 2021) - Luciani, Michela; Rossi, Emanuela; Rebora, Paola; Stawnychy, Michael; Ausili, Davide; Riegel, Barbara
The aims of this study were to describe self-care in US T2DM patients and to identify clinical and sociodemographic determinants of self-care maintenance, monitoring, and management in US T2DM patients. A secondary analysis was performed using data from a cross-sectional study done to test the psychometric performance of the Self-Care of Diabetes Inventory in US English speaking adults with diabetes. In our sample ( n = 207), self-care maintenance was adequately performed (median = 75), self-care monitoring was borderline (median = 67.6) and self-care management was poor (median = 55.6). Low income ( p = .0019) and low self-care confidence ( p < .0001) were associated with relatively lower self-care maintenance. Not taking insulin ( p = .0153) and low self-care confidence ( p < .0001) were associated with relatively low self-care monitoring. Low self-care confidence ( p < .0001) was associated with low self-care management. Self-care confidence is a strong determinant of self-care. Interventions designed to improve self-care confidence are urgently needed.